VALIDITAS LEMBAR KERJA PESERTA DIDIK LKPD BERBASIS INKUIRI TERBIMBING PADA MATERI PEWARISAN SIFAT FASE D SMP/MTs - Oktavia, Velly; Sari, Liza Yulia; Nerita, Siska (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
In the learning process of Phase D science, grade IX has not used the independent curriculum, which will be implemented in the 2023/2024 school year, teachers have utilized various learning media, namely printed books and student worksheets. The use of printed books has not been maximized and the student worksheets used do not meet the components of the worksheet elements. Based on this, a study has been conducted that aims to produce student worksheets based on guided inquiry on the material of inheritance of valid Phase D properties of junior high schools/Islamic junior high schools. This type of research is a 4D model development research. The 4D development model consists of 4 main stages, namely defining, designing, developing, and disseminating. However, the dissemination stage was not carried out in this study. The research instrument consisted of a validity questionnaire, with the validity test carried out by 2 lecturers and 1 science teacher. The results of the data analysis on the validity test of the student worksheet by the validator showed that the worksheet was in the very valid criteria with an average of 91.5%. Based on the research that has been conducted, it can be concluded that the student worksheet based on guided inquiry on the material of inheritance of traits for Phase D in SMP/MTs that was developed is very valid.